Résumés de texte en langue maternelle et en langue seconde : Différences dans l’application des macrorègles entre experts et étudiants de différents niveaux universitaires - Corbeil, Giselle (Canadian Journal of Applied Linguistics, 2010)
This study analyzes the differences between experts and university students of various academic levels in the application of the macrorules of deletion, generalization and construction on text summaries. Learners of French as a second language were required to write a summary of a French text in French, as well as an English text in English, their mother tongue, whereas professors of French and English were asked to do the same thing but only in their mother tongue. Analysis of the results showed that, with regard to the Deletion rule, there are significant differences between French learners and French experts as well as between English experts and the same students. As for the generalization rule, significant differences are also observed between learners of French and French experts, but none when these students are compared to English experts. Similar results are found for the construction rule. Level of proficiency in French has an influence on the application of some rules. Explanations follow and pedagogical suggestions are offered.